Growth and Yield Response of BAU Chia-1 (Salvia hispanica) to Nitrogen Fertilizer (Journal of the Bangladesh Agricultural University, 2024)
Chia (Salvia hispanica L.) is a newly introduced drought-tolerant crop in Bangladesh and registered as BAU chia-1 in 2019 for countrywide cultivation. Its seeds are considered a superfood because of having a large amount (57-65%) of α-linolenic acid (ω-3 fatty acid). This study aims to determine the amount of optimum nitrogen fertilizer to get a good yield in Bangladesh. A field experiment was conducted from November 2023 to February 2024, to assess the influence of nitrogen in the growth and yield of BAU chia-1. A randomized complete block design was conducted with four nitrogen fertilizer treatments (T0 = control/ 0 kg N ha-1, T1= 90 kg N ha-1, T2 = 120 kg N ha-1, T3= 150 kg N ha-1) with three replications. The vegetative growth (plant height, fresh weight plant-1, dry weight plant-1, leaf number plant-1) was higher in the case of T3, but in case of yield contributing attributes (number of inflorescence plant-1, main inflorescence length, number of spikes inflorescence-1, number of spikelet spike-1) and seed yield T2 showed the highest value. Though, SPAD was also the highest in T3, leaf area and fluorescence was higher in T2 than others. Finally, main inflorescence length (39.4 cm), number of inflorescences plant-1 (21), spikes main inflorescence-1 (20), spikelet spike-1 (24) and seed yield (1066 kg ha-1) were higher in T2 treatment than the others. The optimal nitrogen level for BAU chia-1 cultivation appears to be 120 kg N ha-1. However, further multi-location trials are required to validate these findings before making any recommendations.J Bangladesh Agril Univ 22(4): 443-450, 2024